Normative Challenges in Regulating Climate Litigation and Intergenerational Environmental Justice in Contemporary Legal Systems - Ahmad Zuhad Intaha; Akbar Avicenna; Muhammad Ridho Rahman (Lex Recta: Journal of Law and Normative Justice, 2026)
This article examines the normative challenges associated with regulating climate litigation and realizing intergenerational environmental justice within contemporary legal systems. The study is motivated by the increasing reliance on climate litigation as a mechanism for addressing governmental inaction, inadequate climate policies, and the legal protection of future generations whose interests are disproportionately affected by present environmental decisions. Employing a non-empirical legal research design grounded in normative, doctrinal, and comparative legal approaches, the research analyzes international environmental law instruments, constitutional provisions, statutory regulations, judicial decisions, and authoritative legal doctrines concerning climate justice, environmental rights, and intergenerational equity. The analysis demonstrates that contemporary climate litigation is supported by a growing body of international and domestic legal norms recognizing future-oriented environmental obligations, yet its effectiveness remains constrained by doctrinal ambiguities relating to causation, standing, state responsibility, regulatory fragmentation, and judicial enforceability. Comparative examination further reveals an emerging convergence toward the recognition of intergenerational equity as a legally relevant interpretative principle in climate adjudication. The study concludes that a coherent integration of environmental constitutionalism, public trust doctrine, sustainable development, and intergenerational justice is necessary to strengthen climate governance and enhance legal accountability for long-term environmental protection.